Optimisation of a 1,000 year-old antimicrobial recipe - O'Cathail, Colman (2016)
Leechdoms is a term given to medieval era Anglo-saxon remedies which the historian ML Cameron believed to be a meticulous collection of medical texts and knowledge from several cultures. His hypothesis was that these recipes, for years dismissed as useless and ineffective, had merit as medical treatments. In 2015, Harrison et al. published a paper in which they recreated a recipe from a 10th century book known as Bald’s Leechbook. This recipe was that of an eyesalve designed to treat a stye in the eye. The authors showed that their preparation of Bald’s eyesalve proved to be a powerful antimicrobial, effective against antibiotic resistant S. aureus strains. This thesis builds on this work in two ways. First to simplify and optimise the recipe without sacrificing efficacy. Second to refine and isolate active components from the eyesalve to narrow down the list of candidate active components. Attempts to simplify the recipe showed that the wine required in the recipe is key to activity, but is independent of the type of wine used for the preparation. It was demonstrated that the number of days it takes to prepare an active batch of eyesalve can be reduced from nine days to one. The eyesalve remained stable when incorporated into molten agar which was demonstrated to be useful in screening some species for sensitivity to the eyesalves antimicrobial effects. Four different species, S. aureus, K. pneumoniae, A. baumanii and E. coli were screened for growth on eyesalve treated plates and only S. aureus was found to grow, demonstrating that the salve may specifically target certain species of bacteria. Fractionation experiments generated fractions with antimicrobial activity, however the specific method used was not very sensitive and as such narrowed the potential active components to a relatively broad spectrum of compounds. In summary, the data presented here provides significant advancements into understanding how old recipes may have functioned against ancient bacterial infections and provides a unique novel avenue for the discovery of antibiotics.